Ultra-selective detection of sub-ppm-level benzene using Pd–SnO2 yolk–shell micro-reactors with a catalytic Co3O4 overlayer for monitoring air quality. Issue 4 (9th December 2016) - Jeong, Seong-Yong; Yoon, Ji-Wook; Kim, Tae-Hyung; Jeong, Hyun-Mook; Lee, Chul-Soon; Chan Kang, Yun; Lee, Jong-Heun
Abstract : Ultra-selective and sensitive detection of benzene was achieved using Pd-loaded SnO2 yolk–shell micro-reactor sensing films coated with a catalytic Co3 O4 overlayer. Abstract : Ultra-selective and sensitive detection of carcinogenic benzene vapor with negligible interferences from other major indoor pollutants is not only critical but also challenging because the BTX gases (benzene, toluene, and xylene) are generally less reactive to a majority of n-type oxide semiconductor gas sensors and the similar chemical structures of BTX gases hamper their discrimination by chemiresistive variation. Through this paper, we propose a new strategy to detect sub-ppm-level benzene vapor in a highly selective manner using oxide semiconductor chemiresistors. A Pd-loaded SnO2 yolk–shell sensing film coated with a thin catalytic Co3 O4 overlayer showed an ultrahigh response (resistance ratio = 88) to 5 ppm benzene with negligibly low cross-responses to the other representative and ubiquitous indoor pollutants such as toluene, xylene, HCHO, CO, and ethanol. The response to benzene vapor was significantly enhanced by reforming of highly stable benzene into more active and smaller species. The reforming was synergistically assisted by the Co3 O4 catalytic overlayer and sensing layer consisting of Pd-loaded SnO2 micro-reactors, while the cross-responses to the other indoor pollutants became low because of the catalytic oxidation of the gases into less- or non-reactive species. This method will pave a new way to the precise monitoring of critically harmful benzene in both indoor and outdoor atmospheres.